Edukasi Pemanfaatan TOGA dan Pembuatan Produk Disinfektan serta Balsam Stik Berbahan Dasar Lengkuas - Ayuningtyas, Nurista Dida; Hardy, Junius; Pramitaningastuti, Anastasia S; Arianditha Pranasti, Ernestine; Reni Cyrena Santoso, Feronia; Setiawan, Benny (Jurnal Empathy Pengabdian Kepada Masyarakat, 2024)
Background: Batok Village has quite a large agricultural land with the commodity of agricultural products, Alpinia galanga, but the selling value of Alpinia galanga is very cheap. Therefore, the community service team aims to provide education on planting TOGA and making disinfected products and balsam sticks to increase their market value. Methods: Steps taken are observation, preparation, implementation, and evaluation. Results: In the observation, it was observed that Batok Village has agricultural land that is fertile enough for TOGA planting. The preparation process carried out is the manufacture of disinfectant products and balsam sticks with Alpinia galanga as the active ingredient. The Alpinia galanga disinfectant is shown to inhibit the growth of microorganisms, and the resulting balsam stick is solid, easy to apply, produces a warm effect, and does not irritate. Conclusion: The participants were very enthusiastic in participating in the PkM activities, and the results of the evaluation analysis of the participants' knowledge level increased.